THE IMPACT OF GLOBAL TRANSFORMATION ON DECENT WORK IN SOUTH AFRICA - William Manga Mokofe (Obiter, 2024)
This article provides a comprehensive analysis of the impact of global transformation on the concept of decent work in South Africa. By examining the country’s unique historical, social and economic circumstances, the article explores the challenges and opportunities that arise from global dynamics. It investigates various dimensions of decent work affected by global transformation, including employment patterns, wages, working conditions, skills requirements, job security and social protection. The article highlights the need for adaptive strategies to address evolving labour-market dynamics, and emphasises the crucial role of government and stakeholders in promoting decent work. Through collaborative efforts, social dialogue and inclusive policy frameworks, South Africa can effectively navigate global transformation and work towards a labour market that ensures equitable, dignified and fulfilling employment opportunities for all its workers. This research contributes to the academic discourse on the intersection of global transformation, labour markets and decent work, and offers insights and recommendations for policy makers, scholars and practitioners in South Africa and beyond.